The Teaching and Learning of Academic Writing Involving Critical Thinking in Higher Education - Imaniar, Fahmy; Lestari, Lies Amin; Munir, Ahmad (Journal of English Language and Literature (ISSN: 2368-2132), 2018)
Academic writing and critical thinking are two things which strongly deal with higher education context, especially for EFL students. Unfortunately, the process of the teaching and learning which deals with the two aforementioned things was rarely researched. Hence, this current study aimed at revealing the process of teaching and learning of academic writing which involves critical thinking in higher education level. It was carried out through qualitative approach with non-participatory observation and interview as the data collection techniques. The participants were the subject teacher as the one who taught academic writing and also the students in the academic writing class. The result shows that the process of teaching and learning of academic writing consisted of several phases united into a set prevailing for each type of academic writing. Furthermore, critical thinking is engaged within almost all phases with different way of its existence. This study is expected to open eyes towards what occurs in the field, rather than to only value and judge.